Optimization of DNA isolation method from Formalin-Fixed-Paraffin-Embedded tissues (FFPE) and comparative performance of four different Polymerase Chain Reaction (PCR) kits - Zada, Almira; Susanto, Puspasari S.; Putri, Raden L.; Sahiratmadja, Edhyana K.; Hernowo, Bethy S.; Rezano, Andri; Sribudiani, Yunia (Cellular and Molecular Biology, 2018)
The tissue sample may have important genetic information in diagnostic, prognostic and counselling issues. Formalin-Fixed-Paraffin-Embedded (FFPE) is a routine method for preserving tissues. However, DNA isolated from FFPE tissue is often difficult to be amplified in PCR due to fragmentation and DNA-protein crosslinks. This study aimed to optimize the DNA isolation method from FFPE tissue and compare the performance of four different PCR ready-to-use kits. Genomic DNA was isolated from FFPE tissue colon of Short-segment Hirschsprung (S-HSCR) patients and prostate cancer tissue using Quick-DNAâ„¢ FFPE Kit (Zymo Research) with and without pre-heating treatment in KOH/NOH solution. Primers for Androgen Receptor (AR) gene and four different PCR kits: MyTaq HS Red Mix 2X (BioLine), FastStart Taq DNA Polymerase (Roche), KAPA2G fast PCR Kit 2X (KAPA Biosystem) and KOD FX Neo (Toyobo) were used for amplification. DNA electrophoresis was performed to compare the PCR results. BioLine and Toyobo kits gave better PCR results than those of Roche and KAPA Biosystem. Increasing amount of Taq polymerase and dNTPs of Roche kit by two-fold could increase the quality of PCR results. Toyobo could amplify DNA up to 417 bp, however, none of these PCR kits could amplify DNA above 450 bp. Pre-heated treatment of FFPE tissue in NaOH/KOH did not improve the DNA quality and PCR results. Toyobo PCR ready-to-use kit gave the best result among the other three PCR kits used in this study in amplifying DNA isolated from FFPE tissue. Designing the primers producing amplicon not more than 450 bp is suggested.